2015
DOI: 10.1038/srep16277
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/gRNA-directed synergistic activation mediator (SAM) induces specific, persistent and robust reactivation of the HIV-1 latent reservoirs

Abstract: Current antiretroviral therapy does not eliminate the integrated and transcriptionally silent HIV-1 provirus in latently infected cells. Recently, a “shock and kill” strategy has been extensively explored to eradicate the HIV-1 latent reservoirs for a permanent cure of AIDS. The therapeutic efficacy of currently used agents remains disappointing because of low efficiency, non-specificity and cellular toxicity. Here we present a novel catalytically-deficient Cas9-synergistic activation mediator (dCas9-SAM) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 53 publications
4
156
0
Order By: Relevance
“…Significant differences were calculated using a twotailed Student's t-test (** P , 0. Gilbert et al 2014;Chavez et al 2015;Konermann et al 2015;Zhang et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were calculated using a twotailed Student's t-test (** P , 0. Gilbert et al 2014;Chavez et al 2015;Konermann et al 2015;Zhang et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Sporadic breast cancer (i.e., not associated with inherited neoplasia-driving mutations) accounts for the vast majority of breast cancer cases in the U.S. (80-85%) (American Cancer Society 2014). Although ARID1A has not yet been widely recognized as a key suppressor of breast carcinogenesis, it is heterozygously deleted in a substantial fraction of tumors (Cornen et al 2012;Mamo et al 2012), and low ARID1A expression in tumors of patients with breast cancer correlates significantly with poorer prognosis and overall survival (Mamo et al 2011;Zhao et al 2014;Cho et al 2015;Zhang et al 2015). Here, we report functional evidence that Arid1a loss is critical for mammary tumorigenesis in a mouse model of spontaneous breast cancer and present data on how this leads to deregulated cancer cell growth.…”
mentioning
confidence: 99%
“…The combination of Cas9 activators and latency-reversing compounds could promote latent HIV-1 gene activation, which has been proved by dCas9-VP64 and a superior dCas9-SAM systems [27][28][29]. Compare to chemical activating agents, CRISPR/Cas9 system is safer and more efficient though, the balance of "shock" and "kill" is difficult to master.…”
Section: Methods For Eradicating Hiv Reservoirs Activating Then Elimimentioning
confidence: 99%
“…Owing to their poor efficiency and tendencies towards nonspecific and toxic effects, the therapeutic efficacy of the agents currently used in this approach is disappointing. Zhang et al [44] reported a novel catalytically deficient Cas9-synergistic activation mediator technology to allow more selective and potent reactivation of latent HIV-1. Multiple gRNAs were screened and HIV-1 regions were identified that permit induction of robust reactivation of HIV-1 provirus in latently infected cell lines, including the TZM-bI epithelial HeLa cell derivative, Jurkat T lymphocytes, and CHME5 microglia [44].…”
Section: Hiv-1mentioning
confidence: 99%